A comparison trial between three treatment modalities for the management of myofascial pain of jaw muscles: A preliminary study. Issue 5 (3rd September 2018) - Manfredini, Daniele; Favero, Lorenzo; Cocilovo, Francesco; Monici, Monica; Guarda-Nardini, Luca
Abstract: Objectives: To compare three treatment modalities for the management of myofascial pain of jaw muscles. Methods: Thirty ( N  = 30) patients with low pain-related impairment were randomly assigned to receive laser therapy (LST), oral appliance therapy (OA), or counseling (CSL). Visual Analog Scale (VAS) pain levels and the Muscular Index (MI) of the Craniomandibular Index were the outcome variables, which were assessed at baseline, at three weeks, three months, and six months. Results: At six months, improvement in the MI was maintained both in the LST ( p  = .025) and OA groups ( p  < .001). As for VAS values, positive changes were still shown for LST ( p  = .001), and were also shown for the OA ( p  = .002) and CSL groups ( p  = .048). Conclusions: Despite differences in the short-term effectiveness of LST and OA, with respect to CSL alone, all three treatment groups improved at six months. This suggests that active treatments should be directed to maximize the positive changes in the short-term period.